Positive electrode active material and preparation method thereof, positive electrode sheet, secondary battery and electronic device
Through the combination technology of fluorine doping and aluminum-rich and titanium-rich cladding, the problem of poor structural stability of the ternary positive electrode material during deep charging and discharge is solved, and the circulation performance of the secondary battery is significantly improved.
Patent Information
- Application Number
- CN202211035114.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-26
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2042-08-26
AI Technical Summary
Secondary batteries containing ternary positive electrode materials such as nickel, cobalt, manganese, etc. have poor structural stability during deep charging and discharge, resulting in poor circulation performance.
A fluorine-doped ternary positive electrode material matrix is used, and a cladding structure consisting of an aluminum-rich inner cladding layer and a titanium-rich outer cladding layer is formed on its surface. Order doping and coating of fluorine elements is achieved through liquid phase mixing and segmented sintering.
The structural stability and interface stability of the positive electrode active material are improved, and the circulation performance of the secondary battery is significantly improved.
Smart Images

Figure CN115440981B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of electrochemical technology, and in particular to a positive electrode active material and a preparation method thereof, a positive electrode sheet, a secondary battery and an electronic device. Background Art
[0002] Secondary batteries represented by lithium-ion batteries have the advantages of high operating voltage, high energy density, good safety and no memory effect, and have achieved great success in the fields of portable electronic devices, electric vehicles and hybrid vehicles. At present, in traditional secondary batteries, ternary materials such as nickel, cobalt and manganese are widely used as positive electrode materials due to their advantages such as high capacity and energy density. However, secondary batteries containing ternary positive electrode materials such as nickel, cobalt and manganese have poor structural stability during deep charging and discharging, resulting in poor cycle performance. Summary of the invention
[0003] Based on this, the present application provides a positive electrode active material and a preparation method thereof, a positive electrode plate, a secondary battery and an electronic device, aiming to improve the structural stability and cycle performance of the secondary battery.
[0004] The first aspect of the present application provides a positive electrode active material, comprising:
[0005] Fluorine-doped ternary cathode material matrix; and
[0006] A coating structure covering at least a portion of the surface of a fluorine-doped ternary positive electrode material substrate, wherein the coating structure includes an aluminum-rich inner coating layer relatively close to the surface of the fluorine-doped ternary positive electrode material substrate and a titanium-rich outer coating layer relatively far from the surface of the fluorine-doped ternary positive electrode material substrate.
[0007] According to any embodiment of the first aspect of the present application, the positive electrode active material satisfies at least one of the following conditions (1) to (2):
[0008] (1) The fluorine-doped ternary cathode material matrix includes a transition zone, which is distributed in a shallow layer of the fluorine-doped ternary cathode material matrix close to the coating structure, and the transition zone contains AlF 3 ;
[0009] (2) The coating structure further includes a transition layer, which is located between the aluminum-rich inner coating layer and the titanium-rich outer coating layer, and a Li-Al-O-Ti solid solution structure is distributed in the transition layer.
[0010] According to any embodiment of the first aspect of the present application, the positive electrode active material satisfies at least one of the following conditions (1) to (4):
[0011] (1) The average particle size of the positive electrode active material particles is 3 μm to 15 μm;
[0012] (2) The average particle size of the particles of the fluorine-doped ternary cathode material matrix is 3 μm to 15 μm;
[0013] (3) The thickness of the aluminum-rich inner coating layer is 5nm to 100nm;
[0014] (4) The thickness of the titanium-rich outer coating layer is 5 nm to 100 nm.
[0015] According to any embodiment of the first aspect of the present application, the positive electrode active material satisfies at least one of the following conditions (1) to (3):
[0016] (1) The molecular formula of the fluorine-doped ternary cathode material matrix is LiNi x Co y Mn 1-x-y O 2-z F z , where 0.33≤x<0.95, 0.05 <y≤0.77,0<z<1;
[0017] (2) Based on the total mass of the positive electrode active material, the mass percentage of aluminum element in the aluminum-rich inner coating layer is 0.002% to 20%;
[0018] (3) Based on the total mass of the positive electrode active material, the mass percentage of titanium element in the titanium-rich outer coating layer is 0.002% to 20%.
[0019] The second aspect of the present application provides a method for preparing a positive electrode active material, comprising:
[0020] providing a sol containing a fluorine-containing ternary precursor;
[0021] The fluorine-containing ternary precursor sol is mixed with a lithium salt and subjected to a sintering treatment to obtain a fluorine-doped ternary cathode material matrix;
[0022] After the fluorine-doped ternary positive electrode material matrix is mixed with the MAX-type compound-containing coating agent, a secondary sintering treatment is performed to form a coating structure covering at least a portion of the surface of the fluorine-doped ternary positive electrode material matrix, wherein the coating structure includes an aluminum-rich inner coating layer relatively close to the surface of the fluorine-doped ternary positive electrode material matrix and a titanium-rich outer coating layer relatively far from the surface of the fluorine-doped ternary positive electrode material matrix.
[0023] According to any implementation of the second aspect of the present application, the sol of the fluorine-containing ternary precursor is mixed with a lithium salt, and a sintering process is performed, comprising:
[0024] The sol of the fluorine-containing ternary precursor is evenly mixed with the lithium salt and then subjected to ball milling to obtain a pre-doped material;
[0025] The pre-doped material is subjected to a primary sintering treatment at 300° C. to 1000° C., preferably 350° C. to 950° C., for 10 h to 30 h, preferably 15 h to 25 h.
[0026] According to any embodiment of the second aspect of the present application, the preparation method satisfies at least one of the following conditions (1) to (3):
[0027] (1) The molecular formula of the fluorine-doped ternary cathode material matrix is LiNi x Co y Mn 1-x-y O 2-z F z , where 0.33≤x<0.95, 0.05 <y≤0.77,0<z<1;
[0028] (2) Lithium salts include one or more of lithium carbonate, lithium hydroxide, lithium nitrate or lithium acetate;
[0029] (3) The molar ratio of the lithium element in the lithium salt to all transition metal elements in the fluorine-doped ternary positive electrode material matrix is (1.0-1.1):1.
[0030] According to any implementation of the second aspect of the present application, after the fluorine-doped ternary cathode material matrix is mixed with the coating agent containing the MAX type compound, a secondary sintering treatment is performed, which comprises:
[0031] The fluorine-doped ternary cathode material matrix and the coating agent containing the MAX type compound are uniformly mixed and then ball-milled to obtain a pre-coated material;
[0032] The pre-coated material is subjected to a staged sintering treatment to form a coating structure covering at least a portion of the surface of the fluorine-doped ternary positive electrode material matrix to obtain a positive electrode active material.
[0033] According to any implementation of the second aspect of the present application, the staged sintering of the pre-coated material includes:
[0034] Sintering the pre-doped material at 5° C. to 400° C., preferably 50° C. to 450° C., for 1 h to 10 h, preferably 2 h to 8 h, to obtain a first sintered material;
[0035] The first sintering material is sintered at 400° C. to 700° C., preferably 450° C. to 750° C., for 5 h to 30 h, preferably 10 h to 25 h to obtain a positive electrode active material.
[0036] According to any embodiment of the second aspect of the present application, the preparation method satisfies at least one of the following conditions (1) to (3):
[0037] (1) The molecular formula of the MAX type compound coating agent is Ti m AlC n , where 0 <m<5,0<n<5;
[0038] (2) The MAX-type compound-containing encapsulating agent includes nanoparticles of the MAX-type compound, wherein the average particle size of the nanoparticles is 10 nm to 2000 nm;
[0039] (3) The mass ratio of the fluorine-doped ternary positive electrode material matrix to the MAX-type compound-containing coating agent is 1:(0.0005-0.1).
[0040] According to any embodiment of the second aspect of the present application, providing a sol containing a fluorine-containing ternary precursor comprises:
[0041] contacting and mixing a ternary precursor, a dispersant and an aqueous solution containing a fluoride salt to obtain a mixed solution;
[0042] The mixed solution is ball-milled to provide a sol containing a fluorine-containing ternary precursor.
[0043] According to any embodiment of the second aspect of the present application, the preparation method satisfies at least one of the following conditions (1) to (3):
[0044] (1) The solid content of the sol containing the fluorine-containing ternary precursor is 5% to 50%;
[0045] (2) The concentration of the aqueous solution containing the fluoride salt is 0.05 mol / L to 5 mol / L;
[0046] (3) The mass ratio of the ternary precursor, the dispersant and the fluoride salt is 1:(0.001-1.0):(0.001-0.1).
[0047] According to any embodiment of the second aspect of the present application, the preparation method satisfies at least one of the following conditions (1) to (4):
[0048] (1) The molecular formula of the ternary precursor is Ni x Co y Mn 1-x-y (OH) 2 , where 0.33≤x<0.95, 0.05 <y≤0.77;
[0049] (2) the ternary precursor comprises micron particles, and the average particle size of the micron particles is 4 μm to 20 μm;
[0050] (3) the dispersant includes one or more of cetyltrimethylammonium chloride, dodecyltrimethylammonium chloride, cetylpyridinium chloride and sodium benzenesulfonate;
[0051] (4) Fluoride salts include one or more of ammonium fluoride, sodium fluoride, magnesium fluoride and aluminum fluoride, preferably ammonium fluoride.
[0052] The third aspect of the present application provides a positive electrode plate, comprising the positive electrode active material provided in the first aspect of the present application or the positive electrode active material prepared by the preparation method provided in the second aspect of the present application.
[0053] The fourth aspect of the present application provides a secondary battery, comprising the positive electrode plate provided in the third aspect of the present application.
[0054] The fifth aspect of the present application provides an electronic device, comprising the secondary battery provided by the fourth aspect of the present application.
[0055] The electronic device of the present application includes the secondary battery provided by the present application, and thus has at least the same advantages as the secondary battery.
[0056] The positive electrode active material provided in the present application is doped with fluorine element, and the doped fluorine element can enter the lattice of the positive electrode active material bulk phase, inhibiting the lattice distortion caused by the migration of oxygen elements during the cycle process, thereby improving the stability of the crystal structure, reducing the grain boundary cracks and structural collapse caused by the deintercalation of active ions (such as lithium ions) in the crystal structure, improving the structural stability of the positive electrode active material, and then improving the cycle performance of the secondary battery.
[0057] In addition, the coating structure composed of the aluminum-rich inner coating layer and the titanium-rich outer coating layer in the positive electrode active material is uniform and dense, and has high mechanical strength. It can effectively stabilize the electrode / electrolyte interface of the secondary battery positive electrode, and isolate the reaction pathway between the highly oxidized transition metal elements in the positive electrode active material and the electrolyte, thereby reducing the formation of hydrofluoric acid, reducing the dissolution of transition metal elements caused by hydrofluoric acid corrosion on the surface of the positive electrode active material, and weakening the distortion of the surface structure of the positive electrode active material caused by the dissolution of transition metal elements, thereby further improving the interface stability of the secondary battery ternary positive electrode and further improving the cycle performance of the secondary battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0058] Figure 1 1 and 2 are XRD diagrams of the positive electrode active materials of Examples 1 to 2 and Comparative Example 1.
[0059] Figure 2 The following are SEM and EDS images of the positive electrode active material of Example 1.
[0060] Figure 3 It is a comparison chart of the cycle performance of the positive electrode active materials of Examples 1-2 and Comparative Examples 1-2. DETAILED DESCRIPTION
[0061] In order to facilitate the understanding of the present application, the present application will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present application are given in the drawings. However, the present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.
[0062] For simplicity, this application only explicitly discloses some numerical ranges. However, any lower limit can be combined with any upper limit to form an unclearly recorded range; and any lower limit can be combined with other lower limits to form an unclearly recorded range, and any upper limit can be combined with any other upper limit to form an unclearly recorded range. In addition, although not clearly recorded, each point or single value between the range endpoints is included in the range. Thus, each point or single value can be combined with any other point or single value as its own lower limit or upper limit or with other lower limits or upper limits to form an unclearly recorded range.
[0063] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art in the technical field of the present application. The terms used herein in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application. It should be noted that, unless otherwise specified, the term "and / or" used herein includes any and all combinations of one or more related listed items, and "above" and "below" include the number, and the meaning of "multiple" in "one or more" is more than two.
[0064] The above application content of the present application is not intended to describe each disclosed embodiment or each implementation in the present application. The following description more specifically illustrates exemplary embodiments. In many places throughout the application, guidance is provided by a series of examples, which can be used in various combinations. In each example, enumeration is only used as a representative group and should not be interpreted as exhaustive.
[0065] During the research, the inventors found that secondary batteries containing ternary positive electrode materials such as nickel, cobalt and manganese have two major problems during the cycle: (1) During the cycle of the secondary battery, due to the continuous insertion and extraction of active ions (such as lithium ions), the lattice expansion and contraction in the ternary positive electrode material will occur, which can easily lead to grain boundary cracks and crystal structure collapse in the ternary positive electrode material, thereby reducing the cycle performance of the battery; (2) There is an electrode / electrolyte interface reaction at the positive electrode of the secondary battery, especially in a high temperature environment, the electrolyte is easy to react with the highly oxidized Ni in the ternary positive electrode material at the electrode interface. 4+ The reaction produces hydrofluoric acid, which corrodes the electrode interface, leading to the dissolution of a large amount of transition metal elements, causing a further decline in the cycle performance of the secondary battery.
[0066] In order to solve the above-mentioned technical problems, the traditional method is to modify the ternary material by solid-phase doping of elements, such as doping with a single nano-oxide or co-doping with multiple elements, which can improve the stability of the crystal structure of the ternary material to a certain extent, thereby improving its cycle performance; and using inorganic metal oxides, such as aluminum oxide, magnesium oxide, titanium oxide and boron oxide as coating agents to coat and modify the ternary material, to a certain extent avoid direct contact between the ternary material and the electrolyte, reduce the dissolution of transition metal ions, and improve the cycle performance of the secondary battery.
[0067] However, after further research, the inventors found that most of the doping elements in the conventional solid-phase doping method will be distributed in the shallow layer and surface of the ternary material at high temperature, and cannot enter the interior of the material's lattice. In addition, the distribution of the doping elements is uneven, and it is impossible to effectively suppress the grain boundary cracks and crystal structure collapse caused by lithium ion extraction during the cycle, resulting in a decrease in the cycle performance of the secondary battery. In addition, when conventional inorganic metal oxides are used to coat and modify ternary materials, there are also problems such as low and uneven strength of the coating layer and island-like distribution. Subsequently, during the electrode production, rolling and circulation process, the coating layer is prone to cracking and dissolution, resulting in the formation of a new exposed interface, causing continuous structural degradation and performance attenuation of the interface, which will ultimately lead to a decrease in the cycle performance of the secondary battery. In order to at least solve the aforementioned technical problems to a certain extent, the inventors have proposed the following technical solutions.
[0068] A first aspect of an embodiment of the present application provides a positive electrode active material, comprising: a fluorine-doped ternary positive electrode material substrate; and a coating structure coated on at least a portion of the surface of the fluorine-doped ternary positive electrode material substrate, wherein the coating structure comprises an aluminum-rich inner coating layer relatively close to the surface of the fluorine-doped ternary positive electrode material substrate and a titanium-rich outer coating layer relatively far from the surface of the fluorine-doped ternary positive electrode material substrate.
[0069] The positive electrode active material provided in the present application is doped with fluorine. On the one hand, the doped fluorine element can enter the bulk lattice of the positive electrode active material, replace part of the oxygen atoms to form MF chemical bonds (M is Ni, Co or Mn) with stronger bond energy than MO chemical bonds, weaken the migration of oxygen elements during deep charge and discharge cycles, and inhibit the lattice distortion caused by the migration of oxygen elements, thereby improving the stability of the crystal structure, reducing the grain boundary cracks and crystal structure collapse caused by the deintercalation of active ions (such as lithium ions) in the crystal structure, improving the structural stability of the positive electrode active material, and thus improving the cycle performance of the secondary battery. On the other hand, part of the doped fluorine element will remain in the shallow surface layer of the positive electrode active material, forming AlF in the interface layer of the positive electrode. 3 and TiF 3Fluorides such as these can better isolate the electrode / electrolyte interface of the secondary battery, which is beneficial to enhancing the interface stability and improving the cycle performance.
[0070] In some embodiments, the fluorine-doped ternary cathode material matrix includes a transition zone, which is distributed in a shallow layer of the fluorine-doped ternary cathode material matrix near the coating structure, and the transition zone contains AlF 3 .
[0071] In the present application, since the radius of the fluorine atom doped into the bulk phase of the positive electrode active material is smaller than that of the oxygen atom, the fluorine doping will increase the tetrahedral space volume of the lattice of the positive electrode active material, thereby increasing the interlayer spacing to a certain extent, widening the diffusion channel of active ions (such as lithium ions), accelerating the deintercalation rate of active ions in the lattice, and reducing the grain boundary cracks and crystal structure collapse caused by the retention or even accumulation of active ions during the deintercalation process, further improving the stability of the positive electrode active material structure and the cycle performance of the secondary battery. On the other hand, the Ni-F bond with stronger bond energy formed after fluorine doping can reduce the Li + / Ni 2+ The degree of mixing makes the layered structure of the positive electrode active material more orderly and complete, thereby improving its structural stability and further improving the cycle performance of the secondary battery. More importantly, there is a synergistic effect between fluorine doping and coating structure, which is attributed to the fact that F atoms in the shallow surface layer of the crystal can react with alumina in the aluminum-rich inner coating layer to produce AlF 3 , further enhancing the stability of the electrode / electrolyte interface, while also inhibiting the structural degradation of the shallow layer during the cycle process (forming rock salt phase and oxygen defects, etc.) to a certain extent, and enhancing the stability of the crystal structure.
[0072] In some embodiments, the coating structure further includes a transition layer, which is located between the aluminum-rich inner coating layer and the titanium-rich outer coating layer, and a Li-Al-O-Ti solid solution structure is distributed in the transition layer.
[0073] In the present application, the coating structure composed of the aluminum-rich inner coating layer and the titanium-rich outer coating layer in the positive electrode active material has high uniformity and density, high mechanical strength, and can effectively stabilize the electrode / electrolyte interface of the secondary battery positive electrode, isolate the reaction path between the high oxidation state transition metal elements in the positive electrode active material and the electrolyte, thereby reducing the formation of hydrofluoric acid, reducing the dissolution of transition metal elements caused by hydrofluoric acid corrosion on the surface of the positive electrode active material, and weakening the distortion of the surface structure of the positive electrode active material caused by the dissolution of transition metal elements, thereby improving the interface stability of the secondary battery ternary positive electrode and improving its cycle performance. On the other hand, there is a layer of Li-Al-O-Ti solid solution structure similar to a solid electrolyte between the aluminum-rich inner coating layer and the titanium-rich outer coating layer (such as Figure 1-2 As shown in the figure, compared with the relatively "loose" structure of the conventional oxide coating layer, the solid solution formed by Al and Ti elements is denser, has higher lithium ion and electronic conductivity, can better inhibit the dissolution of transition metals on the surface of the material, and improve the rate performance of the material.
[0074] In some embodiments, the average particle size of the positive electrode active material particles is 3 μm to 15 μm. The average particle size of the positive electrode active material within a suitable range is conducive to more uniform mixing between particles, reducing the gaps between particles during mixing, increasing the compaction density of the positive electrode, and improving the rate performance of the secondary battery.
[0075] In some embodiments, the average particle size of the particles of the fluorine-doped ternary cathode material matrix is 3 μm to 15 μm. The average particle size of the particles of the fluorine-doped ternary cathode material matrix is controlled within the above range, which is conducive to improving the uniformity of contact and mixing with the coating agent containing the MAX type compound, and improving the uniformity of the coating agent containing the MAX type compound, thereby improving the uniformity and density of the coating structure.
[0076] In some embodiments, the thickness of the aluminum-rich inner coating layer is 5nm to 100nm, for example, the thickness of the aluminum-rich inner coating layer is 10nm, 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm or within a range consisting of any of the above values.
[0077] In some embodiments, the thickness of the titanium-rich outer coating layer is 5 nm to 100 nm, for example, the thickness of the titanium-rich outer coating layer is 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm or within a range consisting of any of the above values.
[0078] In the embodiment of the present application, if the thickness of the aluminum-rich inner coating layer and the titanium-rich outer coating layer is less than 5nm, the coating effect will be poor and the coating will not be in place; if the thickness of the coating layer is higher than 100nm, the capacity and cycle performance of the secondary battery will decrease, so the thickness of the coating layer needs to be controlled within the above range.
[0079] In some embodiments, the molecular formula of the fluorine-doped ternary cathode material matrix is LiNi x Co y Mn 1-x-y O 2-z F z , where 0.33≤x<0.95, 0.05 <y≤0.77,0<z<1。
[0080] In some embodiments, based on the total mass of the positive electrode active material, the mass percentage of the aluminum element in the aluminum-rich inner coating layer is 0.002% to 20%.
[0081] In some embodiments, based on the total mass of the positive electrode active material, the mass percentage of the titanium element in the titanium-rich outer coating layer is 0.002% to 20%.
[0082] A second aspect of the present application provides a method for preparing a positive electrode active material, comprising the following steps:
[0083] S10, providing a sol containing a fluorine-containing ternary precursor;
[0084] S20, mixing the fluorine-containing ternary precursor sol with a lithium salt, and performing a sintering process to obtain a fluorine-doped ternary positive electrode material matrix;
[0085] S30. After the fluorine-doped ternary positive electrode material matrix is mixed with the MAX-type compound-containing coating agent, a secondary sintering treatment is performed to form a coating structure covering at least a portion of the surface of the fluorine-doped ternary positive electrode material matrix, wherein the coating structure includes an aluminum-rich inner coating layer relatively close to the surface of the fluorine-doped ternary positive electrode material matrix and a titanium-rich outer coating layer relatively far from the surface of the fluorine-doped ternary positive electrode material matrix.
[0086] In the preparation method of the positive electrode active material provided in the present application, the fluorine element is doped (wet doping) by mixing the sol of the fluorine-containing ternary precursor with a lithium salt in the liquid phase and sintering, so that the contact area of the fluorine element on the ternary precursor can be increased, so that the fluorine element can more easily enter the lattice of the ternary material during a single sintering treatment, and realize orderly doping distribution inside the material lattice, forming a strong bond energy MF chemical bond (M is Ni, Co or Mn) in the lattice, weakening the migration of oxygen elements during deep charge and discharge cycles, and inhibiting the lattice distortion caused by the migration of oxygen elements, thereby improving the stability of the crystal structure, reducing the grain boundary cracks and the collapse of the crystal structure caused by the deintercalation of active ions (such as lithium ions) in the crystal structure, improving the structural stability of the positive electrode active material, and then improving the cycle performance of the secondary battery.
[0087] In addition, the secondary sintering treatment can form a coating structure consisting of an aluminum-rich inner coating layer and a titanium-rich outer coating layer. The coating structure has high uniformity and density, high mechanical strength, and can effectively stabilize the electrode / electrolyte interface of the secondary battery positive electrode, isolate the reaction pathway between the highly oxidized transition metal elements in the positive electrode active material and the electrolyte, thereby reducing the formation of hydrofluoric acid, reducing the dissolution of transition metal elements caused by hydrofluoric acid corrosion on the surface of the positive electrode active material, and weakening the distortion of the surface structure of the positive electrode active material caused by the dissolution of transition metal elements, thereby improving the interface stability of the secondary battery ternary positive electrode and improving its cycle performance.
[0088] In some embodiments, providing a sol containing a fluorine-containing ternary precursor in step S10 comprises the following steps:
[0089] S100, contacting and mixing a ternary precursor, a dispersant and an aqueous solution containing a fluoride salt to obtain a mixed solution;
[0090] S110, ball milling the mixed solution to provide a sol containing a fluorine-containing ternary precursor.
[0091] In some embodiments, the solid content of the fluorine-containing ternary precursor sol is 5% to 50%, for example, the solid content can be 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45% or any range thereof. Controlling the solid content within a suitable range is beneficial to improving the utilization rate of the fluorine-containing ternary precursor and avoiding more agglomeration and precipitation.
[0092] Specifically, if the solid content of the mixture of the ternary precursor, the dispersant and the aqueous solution containing the fluoride salt is within the range of 5 to 50%, there is no need to evaporate the water; if the obtained mixed solution is relatively dilute, or a sol with a target solid content is to be obtained, the mixed solution can be placed in a rotary evaporator to evaporate the solvent to obtain a sol with a target solid content.
[0093] In some embodiments, the molecular formula of the ternary precursor is Ni x Co y Mn 1-x-y (OH) 2 , where 0.33≤x<0.95, 0.05 <y≤0.77。
[0094] In some embodiments, the ternary precursor comprises micron particles, and the average particle size of the micron particles is 4 μm to 20 μm, for example, the average particle size of the micron particles is 4 μm, 7 μm, 10 μm, 13 μm, 16 μm, 19 μm or within a range consisting of any of the above values.
[0095] The average particle size of the micron particles contained in the ternary precursor is a well-known meaning in the art and can be measured using instruments and methods known in the art. For example, it can be conveniently measured using a laser particle size analyzer with reference to GB / T 19077-2016 particle size distribution laser diffraction method, such as the Mastersizer 2000E laser particle size analyzer of Malvern Instruments Ltd., UK.
[0096] In some embodiments, the concentration of the aqueous solution containing fluoride salt is 0.05mol / L to 5mol / L, for example, the concentration can be 0.1mol / L, 0.5mol / L, 1mol / L, 1.5mol / L, 2mol / L, 2.5mol / L, 3mol / L, 3.5mol / L, 4mol / L, 4.5mol / L or in the range of any of the above values. The concentration of the aqueous solution of fluoride salt is controlled within a suitable range, which is conducive to obtaining a fluorine-containing ternary precursor with a suitable fluorine element concentration, thereby achieving a better fluorine element doping effect in the subsequent primary sintering process.
[0097] In some embodiments, the type of fluoride salt is not specifically limited and can be selected according to actual needs. For example, the fluoride salt can include one or more of ammonium fluoride, sodium fluoride, magnesium fluoride and aluminum fluoride, preferably ammonium fluoride.
[0098] The use of fluoride salt as a dopant in this application can play the following roles: on the one hand, the electronegativity of fluorine doping is higher than that of oxygen atoms, so after doping, the bond energy between metal atoms and anions in the ternary material can be enhanced, which is conducive to stabilizing the structure; more importantly, after fluorine atom doping, the fluorine atoms doped in the shallow layer can react with the aluminum-rich layer to form AlF with better stability. 3 , effectively stabilizing the structure of the shallow layer and inhibiting the structural reconstruction phenomenon that occurs during the circulation process.
[0099] In some embodiments, the mass ratio of the ternary precursor, the dispersant, and the fluoride salt is 1:(0.001-1.0):(0.001-0.1).
[0100] In some embodiments, the type of dispersant is not specifically limited and can be selected according to actual needs. For example, the dispersant can include one or more of hexadecyltrimethylammonium chloride, dodecyltrimethylammonium chloride, hexadecylpyridinium chloride and sodium benzenesulfonate.
[0101] In some embodiments, the step S20 of mixing the fluorine-containing ternary precursor sol with the lithium salt and performing a sintering process comprises the following steps:
[0102] S200, mixing the sol of the fluorine-containing ternary precursor and the lithium salt uniformly and then ball milling to obtain a pre-doped material;
[0103] S210, performing a primary sintering treatment on the pre-doped material at 300°C to 1000°C, preferably at 350°C to 950°C, for 10h to 30h, preferably for 15h to 25h, to obtain a fluorine-doped ternary positive electrode material matrix.
[0104] In some embodiments, the molecular formula of the fluorine-doped ternary cathode material matrix is LiNi x Co y Mn 1-x-y O 2-z F z , where 0.33≤x<0.95, 0.05 <y≤0.77,0<z<1。
[0105] In some embodiments, the molar ratio of the lithium element in the lithium salt to all transition metal elements in the fluorine-doped ternary positive electrode material matrix is (1.0-1.1):1.
[0106] In some embodiments, the type of lithium salt is not specifically limited and can be selected according to actual needs. For example, the lithium salt can include one or more of lithium carbonate, lithium hydroxide, lithium nitrate and lithium acetate.
[0107] In some embodiments, the temperature of the first sintering process is 300°C to 1000°C, for example, 400°C, 500°C, 600°C, 700°C, 800°C, 900°C or any range thereof. Preferably, the temperature of the first sintering process is 350°C to 950°C.
[0108] In some embodiments, the first sintering treatment time is 10 hours to 30 hours, for example, 15 hours, 20 hours, 25 hours or any range thereof. Preferably, the first sintering treatment time is 15 hours to 25 hours.
[0109] In some embodiments, the sintering atmosphere of the first sintering process is not particularly limited and can be selected according to actual needs. For example, the sintering atmosphere can be air, oxygen, or a mixed atmosphere of air and oxygen.
[0110] In the embodiments of the present application, the temperature and time of the first sintering treatment are both controlled within a suitable range. Through the cooperation of temperature and time, on the one hand, most of the fluorine elements can enter the bulk lattice of the cathode active material, replacing part of the oxygen atoms to form M-F chemical bonds (M is Ni, Co or Mn) with stronger bond energy compared to the M-O chemical bond, weakening the migration of oxygen elements during the deep charge and discharge cycle, and inhibiting the lattice distortion caused by the migration of oxygen elements, thereby improving the stability of the crystal structure, reducing the grain boundary cracks and the collapse of the crystal structure caused by the insertion and extraction of active ions (such as lithium ions) in the crystal structure, improving the structural stability of the cathode active material, and further improving the cycle performance of the secondary battery. On the other hand, there are still some fluorine elements remaining in the shallow surface layer of the cathode active material, forming AlF 3 and TiF 3 and other fluorides in the interface layer of the cathode. These fluorides can better isolate the electrode / electrolyte interface of the secondary battery, which is beneficial to enhancing the interface stability and improving its cycle performance.
[0111] In some embodiments, after the fluorine-doped ternary cathode material matrix and the MAX-type compound coating agent are mixed in step S30, the secondary sintering treatment includes the following steps:
[0112] S300: After the fluorine-doped ternary cathode material matrix and the MAX-type compound coating agent are mixed evenly, ball milling treatment is carried out to obtain a pre-coated material;
[0113] S310: The pre-coated material is subjected to segmented sintering treatment to form a coating structure covering at least part of the surface of the fluorine-doped ternary cathode material matrix, and the cathode active material is obtained.
[0114] In some embodiments, the molecular formula of the MAX-type compound coating agent is Ti m AlC n , where 0 < m < 5 and 0 < n < 5. Preferably, the MAX-type compound coating agent is Ti 3 AlC 2 .
[0115] The present application selects the MAX-type compound as the coating agent mainly for the following reasons: (1) In the MAX-type compound, M and X form a layered structure, and A is an interlayer intercalation element. Its structural characteristics determine that there will be a difference in the activity of M and A elements; (2) The MAX-type compound has a layered structure, which has a large similarity with the ternary material structure. In addition, its electronic conductivity is high, much higher than that of the conventional oxide coating layer (the electronic conductivity of the conventional oxide coating layer is about 10 -4cm / s), and after coating, it can not only inhibit the interfacial reaction, but also improve the electrochemical activity of the coated material, such as rate multiplication; (3) MAX-type compounds are easy to prepare, composed of common elements, with controllable costs and easy industrialization.
[0116] In some embodiments, the MAX compound-containing coating agent includes nanoparticles of the MAX compound, and the average particle size of the nanoparticles is 10 nm to 2000 nm. For example, the average particle size of the nanoparticles is 100 nm, 400 nm, 700 nm, 1000 nm, 1300 nm, 1600 nm, 1900 nm, or within the range of any of the above values. The average particle size of the nanoparticles of the MAX compound is within a suitable range, which can achieve uniform coating and is conducive to the compactness of the coating layer formed subsequently.
[0117] In some embodiments, the mass ratio of the fluorine-doped ternary cathode material matrix to the MAX-type compound-containing coating agent is 1:(0.0005-0.1).
[0118] It should be noted that in order to form a coating structure consisting of an aluminum-rich inner coating layer and a titanium-rich outer coating layer in the positive electrode active material, the pre-doped material needs to be subjected to the following staged sintering treatment in steps S3100 and S3110, and the heating rate during the staged sintering treatment needs to be controlled.
[0119] In some embodiments, the step S310 of performing segmented sintering on the pre-coated material comprises the following steps:
[0120] S3100, sintering the pre-doped material at 5° C. to 400° C., preferably 50° C. to 450° C., for 1 h to 10 h, preferably 2 h to 8 h, to obtain a first sintered material;
[0121] S3110, sintering the first sintered material at 400°C to 700°C, preferably 450°C to 750°C, for 5h to 30h, preferably 10h to 25h, to obtain a positive electrode active material.
[0122] In some embodiments, step S3100 first performs a low temperature sintering process. The temperature of the low temperature sintering process needs to be controlled within a range of 5°C to 400°C, for example, 50°C, 100°C, 150°C, 200°C, 250°C, 300°C, 350°C or within the range of any of the above values; the time needs to be controlled within a range of 1h to 10h, for example, 2h, 4h, 8h or within the range of any of the above values; the heating rate is ≤3°C / min.
[0123] During the low temperature sintering process, by controlling the temperature, time and heating rate within a suitable range, that is, by coordinating the temperature, time and heating rate, the highly active Al element in the MAX type compound coating agent can migrate to the surface to form Al 2 O 3 Nanoparticles are first coated on the surface of the ternary material to form an aluminum-rich inner coating layer. At this time, the coating layer presents an island structure with a relatively loose structure.
[0124] In some embodiments, step S3110 performs high temperature sintering. The temperature of the high temperature sintering needs to be controlled within the range of 400°C to 700°C, for example, 450°C, 500°C, 550°C, 600°C, 650°C or any range thereof; the time needs to be controlled within the range of 5h to 30h, for example, 10h, 15h, 20h, 25h or any range thereof; the heating rate is ≤5°C / min.
[0125] During the high temperature sintering process, by controlling the temperature, time and heating rate within a suitable range, that is, by coordinating the temperature, time and heating rate, the MAX type compound dopant can be completely decomposed to form TiO 2 , and then coating is performed on the basis of the aluminum-rich inner coating layer to form a titanium-rich outer coating layer, thereby obtaining a double-layer coating structure consisting of an aluminum-rich inner coating layer and a titanium-rich outer coating layer. 2 O 3 -TiO 2 Solid solution, so its structure is dense and uniform, with high mechanical strength.
[0126] In some embodiments, the sintering atmospheres of the low-temperature sintering process and the high-temperature sintering process are not particularly limited and can be selected according to actual needs. For example, the sintering atmosphere can be air, oxygen, or a mixed atmosphere of air and oxygen.
[0127] Thus, by performing a segmented sintering treatment, a coating structure consisting of an aluminum-rich inner coating layer and a titanium-rich outer coating layer can be formed. The coating structure has high uniformity and density, high mechanical strength, and can effectively stabilize the electrode / electrolyte interface of the secondary battery positive electrode, isolate the reaction pathway between the high-oxidation state transition metal elements in the positive electrode active material and the electrolyte, thereby reducing the formation of hydrofluoric acid, reducing the dissolution of transition metal elements caused by hydrofluoric acid corrosion on the surface of the positive electrode active material, and weakening the distortion of the surface structure of the positive electrode active material caused by the dissolution of transition metal elements, thereby improving the interface stability of the secondary battery ternary positive electrode and improving its cycle performance.
[0128] A third aspect of the embodiments of the present application provides a positive electrode plate, comprising the positive electrode active material provided in the first aspect of the present application or the positive electrode active material prepared by the preparation method provided in the second aspect of the present application.
[0129] In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector, and the positive electrode film layer includes the positive electrode active material of the second aspect of the present application.
[0130] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.
[0131] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0132] In some embodiments, the positive electrode film layer may also optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0133] In some embodiments, the positive electrode film layer may further include a conductive agent, for example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0134] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0135] A fourth aspect of the embodiments of the present application provides a secondary battery, comprising the positive electrode sheet provided in the third aspect of the present application.
[0136] In some embodiments, the type of secondary battery is not specifically limited, and may include any battery in which an electrochemical reaction occurs to convert chemical energy into electrical energy, for example, a lithium ion battery or a sodium ion battery.
[0137] In some embodiments, the secondary battery further includes a negative electrode sheet, an electrolyte, and a separator. During the battery charge and discharge process, active ions are embedded and removed back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays a role in conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.
[0138] The fifth aspect of the embodiments of the present application provides an electronic device, comprising the secondary battery provided by the fourth aspect of the present application, wherein the secondary battery can be used as a power source in the electronic device.
[0139] In some embodiments, the type of electronic device is not particularly limited, and it can be any electronic device known in the prior art. For example, the electronic device can include, but is not limited to, a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD television, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery, and a lithium-ion capacitor.
[0140] Example
[0141] The following are specific examples, which more specifically describe the contents disclosed in this application, and these examples are only for illustrative purposes, because it is obvious to those skilled in the art that various modifications and variations are made within the scope of the disclosure of this application. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are based on weight, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing, and the instruments used in the examples are commercially available.
[0142] Example 1
[0143] (1) 2.5 kg 4.0 μm Ni 0.6 Co 0.1 Mn 0.3 (OH) 2The ternary precursor and 50g of hexadecyltrimethylammonium chloride were added to 6L of 0.005mol / L ammonium fluoride aqueous solution and ball-milled for 2h to form a sol with a certain solid content. After mixing evenly, the solid content was controlled to be 40% to obtain a sol containing the fluorine-containing ternary precursor;
[0144] (2) 2.0 kg of fluorine-containing ternary precursor sol was mixed with 0.958 kg of lithium carbonate, ball-milled for 2 h, and then sintered, wherein the molar ratio of lithium element in lithium carbonate to alloy element in ternary precursor was Li / (Ni+Co+Mn)=1.053, the sintering temperature was controlled to be 960°C, the sintering time was 12 h, the sintering atmosphere was air, and after sintering, a fluorine-doped ternary cathode material matrix was obtained;
[0145] (3) Take 2.0 kg of fluorine-doped ternary cathode material matrix and 12.5 g of 30 nm Ti 3 AlC 2 After mixing and ball milling for 2 hours, the mixture is sintered in stages. The sintering temperature in the low-temperature stage is 400°C, the sintering time is 4 hours, and the heating rate is 1.5°C / min. The sintering temperature in the high-temperature stage is 650°C, the sintering time is 8 hours, the heating rate is 4°C / min, and the sintering atmosphere is air. After sintering, a fluorine-doped positive electrode active material with a double layer of an aluminum-rich inner layer and a titanium-rich outer layer is obtained.
[0146] Example 2
[0147] (1) 2.5 kg 4.0 μm Ni 0.6 Co 0.1 Mn 0.3 (OH) 2 The ternary precursor and 50g of hexadecyltrimethylammonium chloride were added to 6L of 0.005mol / L ammonium fluoride aqueous solution and ball-milled for 2h to form a sol with a certain solid content. After mixing evenly, the solid content was controlled to be 40% to obtain a sol containing the fluorine-containing ternary precursor;
[0148] (2) 2.0 kg of fluorine-containing ternary precursor sol was mixed with 0.958 kg of lithium carbonate, ball-milled for 2 h, and then sintered, wherein the molar ratio of lithium element in lithium carbonate to alloy element in ternary precursor was Li / (Ni+Co+Mn)=1.053, the sintering temperature was controlled to be 960°C, the sintering time was 12 h, the sintering atmosphere was air, and after sintering, a fluorine-doped ternary cathode material matrix was obtained;
[0149] (3) Take 2.0 kg of fluorine-doped ternary cathode material matrix and 25 g of 30 nm Ti 3 AlC 2After mixing and ball milling for 2 hours, the mixture is sintered in stages. The sintering temperature in the low-temperature stage is 400°C, the sintering time is 4 hours, and the heating rate is 1.5°C / min. The sintering temperature in the high-temperature stage is 650°C, the sintering time is 8 hours, the heating rate is 4°C / min, and the sintering atmosphere is air. After sintering, a fluorine-doped positive electrode active material with a double layer of an aluminum-rich inner layer and a titanium-rich outer layer is obtained.
[0150] Example 3
[0151] (1) 2.5 kg 4.0 μm Ni 0.60 Co 0.1 Mn 0.28 (OH) 2 The ternary precursor and 50g of hexadecyltrimethylammonium chloride were added to 6L of 0.005mol / L ammonium fluoride aqueous solution and ball-milled for 2h to form a sol with a certain solid content. After mixing evenly, the solid content was controlled to be 40% to obtain a sol containing the fluorine-containing ternary precursor;
[0152] (2) 2.0 kg of fluorine-containing ternary precursor sol was mixed with 0.970 kg of lithium carbonate, ball-milled for 2 h, and then sintered, wherein the molar ratio of lithium element in lithium carbonate to alloy element in ternary precursor was Li / (Ni+Co+Mn)=1.060, the sintering temperature was controlled to be 960°C, the sintering time was 12 h, the sintering atmosphere was air, and after sintering, a fluorine-doped ternary cathode material matrix was obtained;
[0153] (3) Take 2.0 kg of fluorine-doped ternary cathode material matrix and 25 g of 30 nm Ti 3 AlC 2 After mixing and ball milling for 2 hours, the materials are sintered in stages. The sintering temperature in the low-temperature stage is 400°C, the sintering time is 4 hours, and the heating rate is 1.0°C / min. The sintering temperature in the high-temperature stage is 650°C, the sintering time is 8 hours, and the heating rate is 10°C / min. The sintering atmosphere is air. After sintering, a fluorine-doped positive electrode active material with a double layer of aluminum-rich inner layer and titanium-rich outer layer is obtained.
[0154] Example 4
[0155] (1) 2.5 kg 15 μm Ni 0.6 Co 0.1 Mn 0.3 (OH) 2 The ternary precursor and 50g of hexadecyltrimethylammonium chloride were added to 12L of 0.005mol / L ammonium fluoride aqueous solution and ball-milled for 2h to form a sol with a certain solid content. After mixing evenly, the solid content was controlled to be 20% to obtain a sol containing the fluorine-containing ternary precursor;
[0156] (2) 2.0 kg of fluorine-containing ternary precursor sol was mixed with 0.998 kg of lithium carbonate, ball-milled for 2 h, and then sintered, wherein the molar ratio of lithium element in lithium carbonate to alloy element in ternary precursor was Li / (Ni+Co+Mn)=1.070, the sintering temperature was 750°C, the sintering time was 15 h, the sintering atmosphere was air, and after sintering, a fluorine-doped ternary cathode material matrix was obtained;
[0157] (3) Take 2.0 kg of fluorine-doped ternary cathode material matrix and 125 g of 30 nm Ti 3 AlC 2 After mixing and ball milling for 2 hours, the mixture is sintered in stages. The sintering temperature in the low-temperature stage is 350°C, the sintering time is 3 hours, and the heating rate is 2.5°C / min. The sintering temperature in the high-temperature stage is 680°C, the sintering time is 10 hours, and the heating rate is 5°C / min. The sintering atmosphere is air. After sintering, a fluorine-doped positive electrode active material with a double-layer coating of an aluminum-rich inner layer and a titanium-rich outer layer is obtained.
[0158] Comparative Example 1
[0159] The preparation method of Comparative Example 1 is similar to that of Example 1, except that the positive electrode active material is not doped or coated. 0.6 Co 0.1 Mn 0.3 (OH) 2 The ternary precursor and lithium hydroxide were mixed evenly according to the molar ratio of lithium element to alloy element of Li / (Ni+Co+Mn)=1.053, and then sintered in a box furnace under oxygen atmosphere with a heating rate of 10°C / min, a sintering temperature of 960°C, and a sintering time of 12h. After jaw crushing, roller crushing and air flow crushing, the undoped and coated positive electrode active material LiNi 0.6 Co 0.1 Mn 0.3 O 2 .
[0160] Comparative Example 2
[0161] The preparation method of Comparative Example 2 is similar to that of Example 2, except that the positive electrode active material is not doped with fluorine, but a double-layer coating treatment of an aluminum-rich inner layer and a titanium-rich outer layer is performed by the staged sintering in the present application, and the specific implementation method is as follows:
[0162] (1) 2.0 kg of the sol of the ternary precursor was mixed with 0.958 kg of lithium carbonate, ball-milled for 2 h, and then sintered, wherein the molar ratio of the lithium element in the lithium carbonate to the alloy element in the ternary precursor was Li / (Ni+Co+Mn)=1.053, the sintering temperature was controlled to be 960° C., the sintering time was 12 h, the sintering atmosphere was air, and the ternary cathode material matrix was obtained after sintering;
[0163] (2) Take 2.0 kg of ternary cathode material matrix and 12.5 g of 30 nm Ti 3 AlC 2 After mixing and ball milling for 2 hours, the mixture is sintered in stages. The sintering temperature in the low-temperature stage is 400°C, the sintering time is 4 hours, and the heating rate is 1.5°C / min. The sintering temperature in the high-temperature stage is 650°C, the sintering time is 8 hours, the heating rate is 4°C / min, and the sintering atmosphere is air. After sintering, a positive electrode active material with a double layer of aluminum-rich inner layer and titanium-rich outer layer is obtained.
[0164] Comparative Example 3
[0165] The preparation method of comparative example 3 is similar to that of example 1, except that the positive electrode active material is only subjected to the liquid phase doping treatment of the fluorine element in the present application, but is not subjected to the coating treatment, i.e., step (3) in example 1 is omitted. The specific implementation method is as follows:
[0166] (1) 2.5 kg 4.0 μm Ni 0.6 Co 0.1 Mn 0.3 (OH) 2 The ternary precursor and 50g of hexadecyltrimethylammonium chloride were added to 6L of 0.005mol / L ammonium fluoride aqueous solution and ball-milled for 2h to form a sol with a certain solid content. After mixing evenly, the solid content was controlled to be 40% to obtain a sol containing the fluorine-containing ternary precursor;
[0167] (2) 2.0 kg of fluorine-containing ternary precursor sol was mixed with 0.958 kg of lithium carbonate, ball-milled for 2 h, and then sintered, wherein the molar ratio of lithium element in lithium carbonate to alloy element in ternary precursor was Li / (Ni+Co+Mn)=1.053, the sintering temperature was controlled to be 960°C, the sintering time was 12 h, the sintering atmosphere was air, and a fluorine-doped ternary cathode material was obtained after sintering;
[0168] Comparative Example 4
[0169] The preparation method of Comparative Example 4 is similar to that of Example 1, except that the positive electrode active material is first doped with fluorine by a conventional dry method, and then coated with an inorganic metal oxide.
[0170] (1) 2.5 kg 4.0 μm Ni0.6 Co 0.1 Mn 0.3 (OH) 2 After the ternary precursor, 0.958 kg of lithium carbonate and 2.2 g of ammonium fluoride were mixed and dry-milled for 2 hours, the molar ratio of lithium element in lithium carbonate to alloy element in the ternary precursor was Li / (Ni+Co+Mn)=1.053, the sintering temperature was controlled to be 960°C, the sintering time was 12 hours, the sintering atmosphere was air, and the fluorine-doped ternary cathode material matrix was obtained after sintering;
[0171] (3) 2.0 kg of fluorine-doped ternary positive electrode material matrix was mixed with 12.5 g of nano-alumina and 10 g of nano-titanium oxide, and the mixture was ball-milled for 2 h and then sintered in stages. The sintering temperature was 600 °C, the sintering time was 8 h, the heating rate was 10 °C / min, and the sintering atmosphere was air. After sintering, a fluorine-doped and aluminum-titanium-coated positive electrode active material was obtained.
[0172] Comparative Example 5
[0173] The preparation method of comparative example 5 is similar to that of example 1, except that in step (3), only one sintering treatment is performed, the sintering temperature is 650° C., the sintering time is 10 h, and the heating rate is 10° C. / min.
[0174] The positive electrode active materials prepared in Examples 1 to 4 and Comparative Examples 1 to 5 or the lithium ions further prepared were subjected to relevant performance tests, and the test results are shown in Tables 1-3 below.
[0175] Among them, the test conditions or test standards for each performance test item are as follows:
[0176] (1) XRD test of positive electrode active materials
[0177] The positive electrode active materials in Examples 1 to 2 and Comparative Example 1 were first cycled for 200 cycles at a voltage of 2.8 V to 4.4 V and a rate of 0.1 C / 0.1 C. The cycled positive electrode active material powder was then placed on a sample stage of an XRD test instrument (model Bruker D8) at a scanning rate of 2° / min and a scanning angle range of 10° to 90° to obtain the following. Figure 1 The XRD diffraction patterns shown. The samples of Examples 1-2 and Comparative Example 1 were subjected to XRD refinement to obtain the refined data shown in Table 1 below; XRD refinement refers to the refinement of XRD data using the Rietveld method.
[0178] (2) SEM and EDS testing of positive electrode active materials
[0179] The positive electrode active material was tested using a ZEISS sigma 300 scanning electron microscope and the sample morphology was observed according to the standard JY / T010-1996. Figure 2 The morphology and EDS spectrum are shown.
[0180] (3) Metal dissolution test of lithium-ion batteries
[0181] For the positive electrode materials prepared in Examples 1-4 and Comparative Examples 1-5, the metal dissolution of the three elements Ni, Co, and Mn was compared after being stored at 80°C for 30 days and 60 days respectively when the battery was fully charged. The test method is as follows: the prepared ternary positive electrode materials were assembled into button batteries, and when the battery was fully charged (4.4V), the batteries were disassembled after being stored at 80°C for 30 days and 60 days respectively, the positive electrode plates were cleaned with DMC, the active material layer of the positive electrode plates was scraped off, and then heated in aqua regia for 15min-30min to dissolve, and the solution was subjected to ICP testing of the Ni, Co, and Mn contents to obtain the data in Table 1. The metal dissolution of the three elements Ni, Co, and Mn was tested, and the test results are shown in Table 2 below.
[0182] (4) High temperature cycle performance test of lithium-ion batteries
[0183] The lithium-ion battery is charged to 4.4V at 1C constant current at 45°C, then charged to a current of 0.1C at constant voltage, left to stand for 5 minutes, and then discharged to 2.8V at 1C constant current. This is one charge and discharge cycle, and the discharge capacity at this time is tested and recorded as D01. The lithium-ion battery is cycled 200 times according to the above charge and discharge process, and the discharge capacity of the 200th cycle is tested and recorded as D1. The test data is recorded in Table 3 below.
[0184] Table 1
[0185]
[0186] From the attached Figure 1 It can be seen that compared with Comparative Example 1, the samples in Examples 1 to 2 have no impurity peaks after cycling, indicating that fluorine doping and coating with aluminum-rich and titanium-rich layers do not change the crystal structure of the positive electrode active material. At the same time, the structure of the material has good stability and no structural abnormality occurs.
[0187] In addition, from the XRD refinement results in Table 1 above, it can be seen that the samples of Examples 1 and 2 have 003 / 104 The strength is greater than that of comparative example 1. This is because the bond energy of the MF bond formed after the positive electrode active material is doped with F is higher than that of the original MO bond (M is Ni, Co or Mn). The MF chemical bond with stronger bond energy can enhance the stability of the crystal structure and reduce the Li + / Ni2+ The degree of mixing makes the layered structure of the material more orderly and complete, thereby improving the structural stability of the positive electrode active material; in addition, the values of the unit cell parameters c, a, c / a and the unit cell volume are all increased. This is because the radius of the F atom is smaller than that of the O atom. After F doping, the volume of the tetrahedral space of the lattice can be increased, thereby increasing the interlayer spacing to a certain extent, broadening the diffusion channel of the active ions (such as lithium ions), and accelerating the deintercalation rate of the active ions in the lattice, thereby further improving the stability of the structure of the positive electrode active material. More importantly, F doping enhances the stability of the unit cell structure and inhibits structural distortion during the cycle process. The direct manifestation is that the half-peak width of the (104) crystal plane of Examples 1 to 2 is significantly higher than that of Comparative Example 1; and the synergistic effect of the surface aluminum-rich and titanium-rich coating layers forms a dense Li-Al-Ti-O solid solution structure, which reduces the "apparent volume" or "apparent size" of the material, and further enhances the stability of the electrode / electrolyte interface. The direct manifestation is that the peak position of the (003) crystal plane of Examples 1 to 2 is smaller than that of Comparative Example 1.
[0188] Table 2
[0189] Group Ni dissolution amount (ppm) Co dissolution amount (ppm) Mn dissolution amount (ppm) Example 1 1085 548 571 Example 2 965 561 588 Example 3 1033 608 612 Example 4 1023 615 621 Comparative Example 1 17434 9302 9540 Comparative Example 2 2322 1012 989 Comparative Example 3 13255 7012 6802 Comparative Example 4 6433 2879 3021 Comparative Example 5 18422 10009 9867
[0190] As can be seen from Table 2, after long-term high-temperature storage, the amount of metal elements dissolved in the ternary positive electrode materials obtained by the preparation method provided by the present application in Examples 1 to 4 is significantly lower than that in Comparative Examples 1 to 5. This shows that F doping can better stabilize the crystal structure and improve the initial efficiency of the material. At the same time, the fluorine-doped and Al- and Ti-coated ternary positive electrode materials obtained by the preparation method provided by the present application can form an effective and stable interface in the lithium-ion battery, which can significantly reduce the interface reaction of the electrode / electrolyte and reduce the formation of hydrofluoric acid, thereby reducing the corrosion of hydrofluoric acid on the surface of the ternary positive electrode material and causing the dissolution of transition metal Ni / Co / Mn elements, which is beneficial to improving the high-temperature storage performance of the lithium-ion battery.
[0191] From the attached Figure 2 As can be seen from the left figure, the positive electrode active material prepared in this application has good dispersibility, the single crystal morphology is round, and a uniform coating layer can be seen on the surface of the material. Figure 2 As can be seen from the right figure, Al, Ti and F elements can be detected on the surface of the material, and the coating layer includes a solid solution formed by Al and Ti oxides.
[0192] Table 3
[0193]
[0194] It can be seen from Table 3 that Examples 1 to 4 have differentiated electrochemical properties from Comparative Examples 1 to 5, and the ternary positive electrode material prepared by the method provided in the present application has better charge and discharge capacity, initial efficiency and cycle performance. It can be seen from the comparison of Examples 1 and 2 and Comparative Example 4 that the charge and discharge capacity, initial efficiency and cycle performance of the ternary positive electrode material obtained by the preparation method provided in the present application are higher than those of the blank sample, the product performance obtained by only fluorine doping or only aluminum-rich and titanium-rich coating processes.
[0195] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0196] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present application shall be subject to the attached claims.
Claims
1. A positive electrode active material, characterized in that: include: Fluorine-doped ternary cathode material matrix; and A coating structure covering at least part of the surface of the fluorine-doped ternary positive electrode material substrate, wherein the coating structure comprises an aluminum-rich inner coating layer relatively close to the surface of the fluorine-doped ternary positive electrode material substrate and a titanium-rich outer coating layer relatively far from the surface of the fluorine-doped ternary positive electrode material substrate; The steps of preparing the fluorine-doped ternary cathode material matrix include: mixing a fluorine-containing ternary precursor sol with a lithium salt, and performing a sintering process; The preparation steps of the coating structure include: mixing the fluorine-doped ternary positive electrode material matrix with a coating agent containing a MAX type compound, and then performing a secondary sintering process.
2. The positive electrode active material according to claim 1, characterized in that The positive electrode active material satisfies at least one of the following conditions (1) to (2): (1) The fluorine-doped ternary cathode material matrix comprises a transition zone, which is distributed in a shallow layer of the fluorine-doped ternary cathode material matrix close to the coating structure, and the transition zone contains AlF3; (2) The coating structure further includes a transition layer, which is located between the aluminum-rich inner coating layer and the titanium-rich outer coating layer, and a Li-Al-O-Ti solid solution structure is distributed in the transition layer.
3. The positive electrode active material according to claim 1, characterized in that The positive electrode active material satisfies at least one of the following conditions (1) to (4): (1) The average particle size of the positive electrode active material particles is 3 μm to 15 μm; (2) The average particle size of the particles of the fluorine-doped ternary cathode material matrix is 3 μm to 15 μm; (3) The thickness of the aluminum-rich inner coating layer is 5 nm to 100 nm; (4) The thickness of the titanium-rich outer coating layer is 5nm~100nm.
4. The positive electrode active material according to any one of claims 1 to 3, characterized in that: The positive electrode active material satisfies at least one of the following conditions (1) to (3): (1) The molecular formula of the fluorine-doped ternary cathode material matrix is LiNi x Co y Mn 1-x-y O 2-z F z , where 0.33≤x<0.95, 0.05 <y≤0.77,0<z<1; (2) Based on the total mass of the positive electrode active material, the mass percentage of aluminum element in the aluminum-rich inner coating layer is 0.002% to 20%; (3) Based on the total mass of the positive electrode active material, the mass percentage of titanium element in the titanium-rich outer coating layer is 0.002% to 20%.
5. A method for preparing a positive electrode active material, characterized in that: include: providing a sol containing a fluorine-containing ternary precursor; The fluorine-containing ternary precursor sol is mixed with a lithium salt and subjected to a sintering treatment to obtain a fluorine-doped ternary cathode material matrix; After the fluorine-doped ternary positive electrode material matrix is mixed with the MAX-type compound-containing coating agent, a secondary sintering treatment is performed to form a coating structure covering at least a portion of the surface of the fluorine-doped ternary positive electrode material matrix, wherein the coating structure includes an aluminum-rich inner coating layer relatively close to the surface of the fluorine-doped ternary positive electrode material matrix and a titanium-rich outer coating layer relatively far from the surface of the fluorine-doped ternary positive electrode material matrix.
6. The preparation method according to claim 5, characterized in that: The sol of the fluorine-containing ternary precursor is mixed with a lithium salt and subjected to a sintering process, which comprises: The sol of the fluorine-containing ternary precursor is evenly mixed with a lithium salt and then subjected to ball milling to obtain a pre-doped material; The pre-doped material is subjected to a primary sintering treatment at 300° C. to 1000° C. for 10 h to 30 h.
7. The preparation method according to claim 6, characterized in that: One or more of the following conditions are met: (1) The pre-doped material is subjected to a sintering treatment at a temperature of 350° C. to 950° C.; (2) The pre-doped material is sintered for 15 to 25 hours.
8. The preparation method according to any one of claims 5 to 7, characterized in that: The preparation method satisfies at least one of the following conditions (1) to (3): (1) The molecular formula of the fluorine-doped ternary cathode material matrix is LiNi x Co y Mn 1-x-y O 2-z F z , where 0.33≤x<0.95, 0.05 <y≤0.77,0<z<1; (2) The lithium salt includes one or more of lithium carbonate, lithium hydroxide, lithium nitrate or lithium acetate; (3) The molar ratio of the lithium element in the lithium salt to all transition elements in the fluorine-doped ternary positive electrode material matrix is (1.0-1.1):
1.
9. The preparation method according to claim 5, characterized in that: After the fluorine-doped ternary cathode material matrix is mixed with the coating agent containing the MAX type compound, a secondary sintering process is performed, which includes: The fluorine-doped ternary cathode material matrix and the MAX-type compound-containing coating agent are uniformly mixed and then ball-milled to obtain a pre-coated material; The pre-coated material is subjected to a staged sintering treatment to form the coating structure covering at least a portion of the surface of the fluorine-doped ternary positive electrode material matrix to obtain the positive electrode active material.
10. The preparation method according to claim 9, characterized in that: The stepwise sintering of the pre-coated material comprises: The pre-coated material is sintered at 5° C. to 400° C. for 1 h to 10 h to obtain a first sintered material; The first sintering material is sintered at 400° C. to 700° C. for 5 h to 30 h to obtain the positive electrode active material.
11. The preparation method according to claim 10, characterized in that: One or more of the following conditions are met: (1) The pre-coated material is sintered at a temperature of 50°C to 450°C; (2) The pre-coated material is sintered for 2 hours to 8 hours; (3) The temperature of sintering the first sintering material is 450° C. to 750° C.; (4) The sintering time of the first sintering material is 10 hours to 25 hours.
12. The preparation method according to any one of claims 5 to 7, characterized in that: The preparation method satisfies at least one of the following conditions (1) to (3): (1) The molecular formula of the MAX-type compound coating agent is Ti m AlC n , where 0 <m<5,0<n<5; (2) The MAX-type compound-containing coating agent comprises nanoparticles of the MAX-type compound, and the average particle size of the nanoparticles is 10 nm to 2000 nm; (3) The mass ratio of the fluorine-doped ternary cathode material matrix to the MAX-type compound-containing coating agent is 1:(0.0005-0.1).
13. The preparation method according to any one of claims 5 to 7, characterized in that: The sol containing the fluorine-containing ternary precursor comprises: contacting and mixing a ternary precursor, a dispersant and an aqueous solution containing a fluoride salt to obtain a mixed solution; The mixed solution is subjected to ball milling treatment to provide a sol of the fluorine-containing ternary precursor.
14. The preparation method according to claim 13, characterized in that: The preparation method satisfies at least one of the following conditions (1) to (3): (1) The solid content of the sol of the fluorine-containing ternary precursor is 5% to 50%; (2) The concentration of the aqueous solution containing fluoride salt is 0.05 mol / L to 5 mol / L; (3) The mass ratio of the ternary precursor, the dispersant and the fluoride salt is 1:(0.001~1.0):(0.001~0.1).
15. The preparation method according to claim 13, characterized in that: The preparation method satisfies at least one of the following conditions (1) to (4): (1) The molecular formula of the ternary precursor is Ni x Co y Mn 1-x-y (OH)2, where 0.33≤x<0.95, 0.05 <y≤0.77; (2) The ternary precursor comprises micron particles, and the average particle size of the micron particles is 4 μm to 20 μm; (3) The dispersant includes one or more of hexadecyltrimethylammonium chloride, dodecyltrimethylammonium chloride, hexadecylpyridinium chloride or sodium benzenesulfonate; (4) The fluoride salt includes one or more of ammonium fluoride, sodium fluoride, magnesium fluoride or aluminum fluoride.
16. The preparation method according to claim 15, characterized in that: The fluoride salt is ammonium fluoride.
17. A positive electrode plate, characterized in that: The invention comprises the positive electrode active material according to any one of claims 1 to 4 or the positive electrode active material prepared by the preparation method according to any one of claims 5 to 16.
18. A secondary battery, characterized in that: Including the positive electrode sheet as described in claim 17.
19. An electronic device, characterized in that: Includes the secondary battery as claimed in claim 18.
Citation Information
Patent Citations
Coated ternary positive electrode material, preparation method thereof and lithium ion battery
CN112993259A
Positive electrode active material for lithium ion secondary battery, method for manufacturing the same, positive electrode for lithium ion secondary battery, and lithium ion secondary battery
JP2020047545A